Transitional justice and the spaces of memory activism in Timor-Leste and Aceh. Issue 2 (4th May 2019) - Kent, Lia
ABSTRACT: Taking Timor-Leste and Aceh, Indonesia, as case studies, this article examines the spaces that are imagined and created by activist-led commemorations of conflict-related violence. Focusing on recent commemorations of the Liquica Church Massacre in Timor-Leste and Simpang KKA in Aceh, it uncovers how these memory spaces are shaped and constrained by the interplay between the globally circulating discourse of transitional justice and the power dynamics resulting from the respective peace settlements. At the same time, it posits that these examples of memory activism contain creative possibilities for encouraging public debate and democratic participation, and for locally grounded forms of mourning. This is due to the multiple, dynamic, relational, spaces that emerge from the embodied encounters of those present at the commemorations.